Anti-TNF biosimilars in rheumatology: the end of an era?. (2nd January 2021) - Dey, Mrinalini; Zhao, Sizheng Steven; Moots, Robert J.
ABSTRACT: Introduction: Tumor necrosis factor inhibitors (TNFi) have revolutionized the treatment of rheumatic diseases. Whilst extremely efficacious, the original TNFi also carried a high acquisition cost that limited their use. 'Biosimilar' TNFi's, developed on expiry of the patents for the biooriginators, have comparable efficacy and safety, are less expensive and provide the potential to improve access to these effective therapies in a more cost-effective manner. Areas covered: The background and development of TNFis, their biosimilars and follow on 'copycat' drugs are discussed, together with their use in both developed and developing countries, focusing on the potential to enhance access to effective targeted therapies. Expert opinion: Bridging the economic gap to facilitate universal access to anti-TNF biosimilars has been largely unsuccessful, driving the development of copycat mimics in developing countries. Meanwhile, the more recent introduction of targeted synthetic disease-modifying drugs has provided cheaper, equally effective treatments for rheumatic diseases that are conveniently delivered by mouth. We review the TNF biosimilars in rheumatic diseases, their role in a rapidly evolving treatment landscape, and speculate about the future for this iconic therapeutic class.